Sustainable housing complex with bioclimatic technologies for the minimum environmental impact in Calana - Caldas Alberca, Robert Paul Alexander (2014)
Objective: This research work aims to develop the architectural project "residential block with bioclimatic technologies" in the district of Calana to reduce the housing deficit in the department of Tacna causing minimal environmental impact on the site. Method: It has required the application of descriptive and explanatory type of research. For this case, moreover, requires statistical methods as it will determine how to proceed with establishing the architectural proposal. Results: an architectural project that not only solve the housing shortage, but give quality spaces and generate a minimal impact on the environment and the environment with the correct use of bioclimatic technologies to use natural resources is proposed. This will affect the following: Social: Housing quality and comfort meet user needs. Economic: By harnessing renewable and non- renewable resources to long-term savings is generated. Urbano-Environmental: Thanks to the different bioclimatic technologies have a positive impact on the environment and the population is generated. Why the proposal of sustainable residential block with bioclimatic technologies for minimal environmental impact develops Calana. Conclusions: Today, the conception, design and construction of housing becomes a nodal point of sustainable development, which involves the integration of the meanings of care and no deterioration of the environment, not only as a housing unit but even as a component of the urban fabric where it is located, therefore, proposes an infrastructure in this regard as sustainable solution edgy character.